How low did we go? A case report of unexpected thrombocytopenia. (May 2019) - Meng, M.L.; Wang, E.; Cain, C.; Landau, R.
Highlights: The risk of spinal-epidural hematoma with a platelet count <50 000/μL is unknown. Neuraxial labor analgesia is often withheld if the platelet count is <50 000/μL. Cases performed when the platelet count is <50 000/μL should be reported. Abstract: We report the case of a normotensive 31-year-old parturient who received combined spinal-epidural analgesia for early labor, and who was then found to have an unexpectedly low platelet count (25 000/μL) with elevated liver enzymes, but without alterations in blood pressure.